THE IMPACT OF THE COVID-19 PANDEMIC ON PHYSICAL ACTIVITY AMONG DENTAL STUDENTS - Đorđević, Jana; Cvorovic, Tamara; Jovanovic, Svetlana; Milosevic Markovic, Maja (Medicinski podmladak, 2024)
Introduction: The pandemic of COVID-19 and epidemiological recommendations adopted to prevent the spread of infection, can significantly impact on physical and mental health of all group population. Although dental students are not a vulnerable group, due to the inability to complete develop of their clinical skills during their education they were particularly affected by pandemic. In reducing the stress caused by the pandemic, physical activity can play a significant role. The aim of study was to measure the impact of COVID-19 on physical activity among dental students. Material and Methods: The online research was conducted between 01 to 26 December 2020, during the winter semester of the 2020/21 school year at the School of Dental Medicine, University of Belgrade. The study includes 379 dental students (305 female and 74 male) with average age 21.6 ± 2.6 years. As a research instrument, demographic questionnaire which contains question about sex, age, year of studies, material status, place of residence, smoking status and alcohol consuming, anthropometric data (weight, height and waist circumference) and International Physical Activity Questionnaire (IPAQ) was used. Results: Тhere is a statistically significant reduction of physical activity, on all levels, during the pandemic (p< 0.05). Students spend 2 hours more sedentary than before the pandemic. The number of students with high physical activity decreased, while the number of those with moderate and low physical activity increased. The total MET is lower during the pandemic than before (p< 0.05). There is a statistically significant difference in the frequency and intensity of physical activity expressed in MET between the sexes before and during the pandemic (p< 0.05). Conclusion: During pandemic, physical activity of dental students is significantly reduced, particularly in female students. It is necessary to take preventive measures so that an excessively sedentary lifestyle would not compromise the students health.